Catalytic Asymmetric [8+2] Annulation Reactions Promoted by a Recyclable Immobilized Isothiourea. Issue 47 (23rd October 2017) - Wang, Shoulei; Rodríguez‐Escrich, Carles; Pericàs, Miquel A.
Abstract: Higher‐order cycloaddition reactions constitute an efficient approach towards the construction of medium to large ring systems. However, enantioselective versions of these transformations remain scarce, which hampers their deployment in medicinal chemistry, or any other discipline in which homochirality is deemed crucial. Herein, we report a novel method for the production of enantiomerically enriched cycloheptatrienes fused to a pyrrolidone ring on the basis of an isothiourea‐catalyzed periselective [8+2] cycloaddition reaction between chiral ammonium enolates (generated in situ from carboxylic acids) and azaheptafulvenes. The resulting bicyclic compounds can be hydrogenated, but, most remarkably, they can also undergo completely regioselective [4+2] cycloaddition with active dienophiles to give architecturally complex polycyclic compounds in a straightforward manner. Abstract : Always ready for more : A periselective [8+2] cycloaddition between chiral ammonium enolates and azaheptafulvenes with a recyclable isothiourea catalyst provided enantiomerically enriched cycloheptatrienes fused to a pyrrolidone ring (see scheme). Derivatization of these versatile cycloadducts through a further regio‐ and diastereoselective cycloaddition reaction led to architecturally complex polycyclic compounds.